PIV-measurements of reactant flow in hydrogen-air explosions. (2nd April 2019) - Vaagsaether, K.; Gaathaug, A.V.; Bjerketvedt, D.
Abstract: The paper present the work on PIV-measurements of reactant flow velocity in front of propagating flames in hydrogen-air explosions. The experiments was performed with hydrogen-air mixture at atmospheric pressure and room temperature. The experimental rig was a square channel with 45 × 20 mm 2 cross section, 300 mm long with a single cylindrical obstacle of blockage ratio 1/3. The equipment used for the PIV-measurements was a Firefly diode laser from Oxford lasers, Photron SA-Z high-speed camera and a particle seeder producing 1 μm droplets of water. The gas concentrations used in the experiments was 14 and 17 vol% hydrogen in air. The resulting explosion can be characterized as slow since the maximum flow velocity of the reactants was 13 m/s in the 14% mixture and 23 m/s in the 17% mixture. The maximum flow velocities was measured during the flame-vortex interaction and at two obstacle diameters behind the obstacle. The flame-vortex interaction contributed to the flame acceleration by increasing the overall reaction rate and the flow velocity. The flame area as a function of position is the same for both concentrations as the flame passes the obstacle. Highlights: Flame surface areas are same for 14 and 17% hydrogen in air as function of position. Flame-vortex interaction produce wrinkled flames not turbulent. Velocity field can be used for comparison and validation of CFD-codes.